The Relationship Between Caffeine Consumption and Sleep Quality among Teenagers in Lahore, Pakistan: Relationship Between Caffeine Consumption and Sleep Quality among Teenagers - Ikram, Mashta; Hameeda, Maryam; Fatima, Ayesha; Naeem, Waleeja; Nadeem, Rabiya; Akmal, Asma; Akram, Naveen (Pakistan Journal of Health Sciences, 2025)
Caffeine, a widely consumed stimulant, is prevalent among teenagers, particularly through beverages like tea, coffee, energy drinks, and soft drinks. As sleep is vital for physical and mental development in teenagers, increased caffeine intake may adversely affect their sleep quality. However, limited research exists on this association within the Pakistani context, particularly in urban centers. Objectives: To evaluate the relationship between caffeine consumption and sleep quality among teenagers in Lahore. Methods: An analytical cross-sectional study was conducted among 400 teenagers aged 13–19 years from selected schools and colleges in Lahore. Data were collected using a structured questionnaire that incorporated the Caffeine Consumption Questionnaire (CCQ) and the Pittsburgh Sleep Quality Index (PSQI). The CCQ assessed the frequency and quantity of caffeine intake, while the PSQI evaluated the participants’ sleep quality. Participants were grouped based on caffeine consumption levels (low, moderate, high). Statistical analysis, including chi-square tests and logistic regression, was performed using SPSS to determine associations. Results: Many teens regularly consumed caffeine through tea or coffee, as revealed in our findings, which showed that 45.5% of teens consumed it daily and 31% consumed it frequently. The research showed that 68% of participants get poor sleep according to PSQI results, which indicates serious public health risks. Conclusions: The analysis revealed caffeine consumption led to poor sleep quality for teenagers according to research data.